Kedudukan Undang-Undang Perlindungan Anak Terhadap Anak Sebagai Korban Pelecehan Seksual di Aceh - Krisna Nanda Aufa (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
This article is motivated by the number of cases of sexual harassment that have occurred in Aceh Province today, experienced by children and adolescents, especially women. In general, victims of sexual harassment are children and adolescents who are under 18 years of age, only in some cases of sexual harassment where the victim is an adult woman. As for one of the legal efforts made by the Banda Aceh Police Criminal Unit by using the Child Protection Law related to the case of children as victims of sexual harassment. The formulation of the problem in this research is what is the position of the Child Protection Law against children as victims of sexual harassment in Aceh and why Polri investigators apply the Child Protection Law instead of the Qanun in enforcing law enforcement. The aim of this research is to find out and explain the position of the Child Protection Law against children as victims of sexual harassment in Aceh and to find out and explain that Police Investigators apply the Child Protection Law compared to Qanun in enforcing law enforcement. This research is a field research (field research) using qualitative methods that collect data through observation and interviews. When viewed from the use of laws used by investigators of the Banda Aceh Police Criminal Investigation Unit from 2018 to September 2020 with a total of 45 cases both completed and in the process of investigation and investigation, all using the Child Protection Law, none. using both the Qanun and the Criminal Code. If the investigator applies the Qanun for perpetrators of sexual violence against children and it is feared that a potential conflict or problem will occur between the victim and the perpetrator if the investigator continues to use the Qanun, that perpetrators of sexual violence against children will be sentenced to imprisonment instead of being punished by caning so that This is considered to provide a sense of justice for the victim and will have a deterrent effect on the perpetrator. Artikel ini dilatarbelakangi oleh banyaknya kasus pelecehan seksual yang terjadi di Provinsi Aceh saat ini yang dialami oleh anak-anak dan remaja khususnya perempuan. Pada umumnya korban pelecehan seksual adalah anak-anak dan remaja yang berusia di bawah 18 tahun, hanya pada beberapa kasus pelecehan seksual dimana korbannya adalah wanita dewasa. Adapun salah satu upaya hukum yang dilakukan oleh Satuan Reserse Kriminal Polres Banda Aceh dengan menggunakan UU Perlindungan Anak terkait kasus anak sebagai korban pelecehan seksual. Rumusan masalah dalam penelitian ini adalah bagaimana kedudukan UU Perlindungan Anak terhadap anak sebagai korban pelecehan seksual di Aceh dan mengapa penyidik ​​Polri menerapkan UU Perlindungan Anak bukan Qanun dalam penegakan hukum. Penelitian ini bertujuan untuk mengetahui dan menjelaskan kedudukan UU Perlindungan Anak terhadap anak sebagai korban pelecehan seksual di Aceh serta untuk mengetahui dan menjelaskan bahwa Penyidik ​​Polri menerapkan UU Perlindungan Anak dibandingkan dengan Qanun dalam penegakan hukum. Penelitian ini merupakan penelitian lapangan (field research) dengan menggunakan metode kualitatif yang mengumpulkan data melalui observasi dan wawancara. Jika dilihat dari penggunaan hukum yang digunakan penyidik ​​Satuan Reserse Kriminal Polres Banda Aceh dari tahun 2018 sampai dengan September 2020 sebanyak 45 kasus baik yang sudah selesai maupun dalam proses penyidikan dan penyidikan semuanya menggunakan UU Perlindungan Anak tidak ada. menggunakan Qanun dan KUHP. Jika penyidik ​​menerapkan Qanun bagi pelaku kekerasan seksual terhadap anak dan dikhawatirkan akan terjadi potensi konflik atau masalah antara korban dan pelaku jika penyidik ​​terus menggunakan Qanun, maka pelaku kekerasan seksual terhadap anak akan dipidana. dipidana penjara bukannya dihukum cambuk sehingga hal ini dianggap memberikan rasa keadilan bagi korban dan akan memberikan efek jera bagi pelaku.